2012
DOI: 10.1177/0883073812460093
|View full text |Cite
|
Sign up to set email alerts
|

The Optic Disc Is Minimal in Children With Idiopathic Intracranial Hypertension

Abstract: This study sought to characterize the optic disc morphology, particularly the cup-to-disc ratio of the optic nerve head in children with idiopathic intracranial hypertension. The medical charts and digital optic disc photos of children with confirmed diagnosis of idiopathic intracranial hypertension were reviewed retrospectively. The optic disc area, cup area, and cup-to-disc ratio were measured digitally using VISUPAC software, and the mean values of those parameters were compared to the published norms. Of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Because a small cup-to-disk ratio is known to be a risk factor for PTCS, some have suggested that patients with intracranial hypertension without papilledema are more likely to have a larger cup-to-disk ratio, which may protect against the development of papilledema. 31 The absence of papilledema is reported with similar frequency in children as in adults. However, in contrast to adults, the degree of opening pressure elevation does not appear to be associated with the presence of papilledema in children.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Because a small cup-to-disk ratio is known to be a risk factor for PTCS, some have suggested that patients with intracranial hypertension without papilledema are more likely to have a larger cup-to-disk ratio, which may protect against the development of papilledema. 31 The absence of papilledema is reported with similar frequency in children as in adults. However, in contrast to adults, the degree of opening pressure elevation does not appear to be associated with the presence of papilledema in children.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, among adult patients with opening pressure above the upper limit of normal, those with papilledema have been found to have higher opening pressures than those without papilledema, and the data here confirmed this finding in a pediatric population. Because a small cup‐to‐disk ratio is known to be a risk factor for PTCS, some have suggested that patients with intracranial hypertension without papilledema are more likely to have a larger cup‐to‐disk ratio, which may protect against the development of papilledema . The absence of papilledema is reported with similar frequency in children as in adults.…”
Section: Discussionmentioning
confidence: 99%
“…10 Likewise, translaminar pressure with subsequent optic nerve damage in primary open angle glaucoma (POAG) can manifest as a typical glaucomatous cupping with an increased CDR. 11 Although two previous studies of IIH have documented a smaller CDR in patients with IIH with papilloedema (IIHWP) as compared with normal subjects, 13,14 to our knowledge, no prior study has examined the CDR in patients with IIHWOP. Based upon our initial clinical impressions about CDR in IIH, we hypothesised that, as in NAION, a small CDR might be a structural risk factor for the development of IIHWP and a larger CDR might be associated with IIHWOP.…”
Section: Introductionmentioning
confidence: 96%
“…It has been proposed that a larger optic cup-to-disk ratio might allow for some modulation, possibly delaying the onset of appreciable papilledema. 20…”
Section: Discussionmentioning
confidence: 99%